Respon Hasil Produksi Kacang Tanah (Arachis hypogea) terhadap Aplikasi PGPR dan Rhizobium - Prayudi, Angga; Wardana, Rudi; Erdiansyah, Iqbal (Politeknik Negeri Jember, 2025)
Increasing peanut production can be done by applying rhizobium and PGPR. This study aims to examine the effect of PGPR and Rhizobium on peanuts. The research was conducted from December 2022 to February 2023 in Patemon Village, Pakusari District, Jember Regency. Experimental design using factorial RAK. The first factor was the concentration of PGPR consisting of 10.5 ml/l, 12.5 ml/l and 14.5 ml/l. The second factor was the dose of Rhizobium inoculants consisting of 25 kg/ha, 50 kg/ha, and 75 kg/ha. The results of this study indicated that there was no real interaction between the PGPR and Rizobum treatments. As a single factor, PGPR with a concentration of 12.5 ml/l gave an effect on the variable number of ginophores (72.1). While the application of Rhizobium inoculant at a dose of 75 kg/ha showed the best results on the number of pods/sample (30.90), weight of pods/sample (62.12 g), weight of seeds/sample (44.74 g), and weight of seeds/plot (850.60 gr). . It is suspected that the application of PGPR to peanuts and inoculation of Rhizobium plays a role in increasing nutrient uptake which in turn increases growth and production.